THE DEVELOPMENT AND SPECIFICS OF REGIONAL MODELS OF THE HUMAN RIGHTS COMMISSARYINSTITUTION IN RUSSIA - Yuriy Nikolaevich Kulik (Современная наука и инновации)
A striking feature of the past 20 years has been the spread of the human rights commissary institution throughout Russia. Mandated to protect citizens ' fundamental rights, ombudsmen have become a recognized and legitimate resource for citizens in many regions. Situating the analysis within the field of political science - the role of institutions in processes of democratisation and rights protection - this paper is motivated by the broad purpose of attempting to understand some of the implications of the development of the human rights ombudsmen in the Russian context, with particular focus on the political processes that underlie its ability to enhance political accountability and rights protection.